The concept of wealth in the view of maqashid al-sharia - Naerul Edwin Kiky Aprianto (Department of Islamic Economics, Islamic University of Indonesia, 2017)
Fundamentally, Islam is a religion which perfectly encompasses all aspects of human life. Wealth in the Islamic economic system has an important position. In its relation to the economic business activities and the rituals of worship, the wealth is given close attention so that in the maqashid al-sharia makes it into one of the essential points, which is to maintain or protect the wealth. These are Allah’s purpose and aim in order to bring benefits to people and serve as a guide in doing business and transaction in accordance to sharia. The use of wealth in Islamic teaching should always be in dedication to Allah and utilized in order to taqarrub (draw yourself closer) to Allah. The personal wealth must be utilized not only for the owners’ private use, but also for social function in order to help fellow human beings. Islam has given special attention to wealth, on how to both get and utilize it, so that the wealth owned has the values of worship on Allah’s side in the pursuit of happier life in the hereafter.